Zika virus outbreak in Brazil - Jorg Heukelbach; Carlos Henrique Alencar; Alyson Ann Kelvin; Wanderson Kleber de Oliveira; Luciano Pamplona de Góes Cavalcanti (Journal of Infection in Developing Countries)
Zika virus (ZIKV) infection is spreading rapidly within the Americas after originating from an outbreak in Brazil. We describe the current ZIKV infection epidemic in Brazil and the neurological symptoms arising. First cases of an acute exanthematic disease were reported in Brazil’s Northeast region at the end of 2014. In March 2015, autochthonous ZIKV was determined to be the causative agent of the exanthematic disease. As cases of neurological syndromes in regions where ZIKV, dengue and/or Chikungunya viruses co-circulate were reported, ZIKV was also identified in the cerebrospinal fluid of patients with acute neurological syndromes and previous exanthematic disease. By the end of September 2015, an increasing number of infants with small head circumference or microcephaly were noted in Brazil’s Northeast which was estimated to be 29 cases between August and October. ZIKV was identified in blood and tissue samples of a newborn and in mothers who had given birth to infants with microcephaly and ophthalmological anomalies. In 2015, there were an estimated 440,000 - 1,300,000 Zika cases in Brazil. There have been 4,783 suspected cases of microcephaly, most of them in the Northeast of Brazil associated with 76 deaths. The Ministry of Health is intensifying control measures against the mosquito Aedes aegypti and implemented intensive surveillance actions. Further studies are needed to confirm the suspected association between ZIKV infection and microcephaly; to identify antiviral, immunotherapy, or prophylactic vaccine; to introduce diagnostic ELISA testing. Clinical and epidemiological studies must be performed to describe viral dynamics and expansion of the outbreak.